Tunable microscopic aggregation morphology of α-Ni(OH)2 for enhanced photocatalytic degradation of fracturing flowback fluid with ozone synergy - Yang, Huohai; Tang, Xinrui; Li, Renze; Liu, Xuanyu; Zhang, Ping; Gong, Yeqi (Frontiers in Materials, 2022)
In this study, hydrothermal synthesis was used to prepare α-Ni(OH)2, which is a steady-state photocatalytic material. Furthermore, ball milling was used for the 1:1 loading of α-Ni(OH)2 with nano-alumina (Al2O3), hexagonal boron nitride (h-BN), and activated carbon (AC). The performances of these four materials in the degradation of a fracturing flowback fluid were investigated under the synergistic catalytic effect of ozone. The results showed that under this effect, the α-Ni(OH)2/nano -Al2O3 photocatalyzed the formation of active hydroxyl radicals (·OH) and superoxide radicals (·O2−), which in turn degraded the return solution. Although ozone itself can spontaneously form certain ·OH and O2− in water, compared to α-Ni(OH)2, the nano- Al2O3 with a higher valence band of 0.2eV provided more active sites and better electron migration efficiency for the conversion of ozone, improving the conversion efficiency of this process (Figure 11). In addition, unlike the other two types of carriers, nano-Al2O3 could provide intergranular support for nanopillared α-Ni(OH)2, increasing the specific surface area and the number of active sites.